2009
DOI: 10.1016/j.janxdis.2008.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Generalized anxiety disorder in a nonclinical sample of children: Symptom presentation and predictors of impairment

Abstract: Presentation of generalized anxiety disorder (GAD) in a nonclinical sample of children (7–11 years old) and factors that predict overall impairment were examined. Symptom presentation was compared in children with GAD (n = 49) and anxious children without GAD (n = 42). Children with GAD endorsed significantly more worries, greater intensity of worries, and more DSM-IV associated symptoms than anxious children without GAD. Eighty-six percent of children with GAD had a comorbid diagnosis with 4% having a depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 22 publications
1
19
0
5
Order By: Relevance
“…10 From a sensitivity standpoint, similar to previous GAD research with children 17,18 there was strong support in the present sample for the inclusion of restlessness as an associated symptom. However, from a sensitivity standpoint there was weak support for the inclusion of muscle tension, which showed the lowest prevalence among GAD cases and the least favorable sensitivity properties across the DSM-IV associated symptoms.…”
Section: Discussionsupporting
confidence: 87%
“…10 From a sensitivity standpoint, similar to previous GAD research with children 17,18 there was strong support in the present sample for the inclusion of restlessness as an associated symptom. However, from a sensitivity standpoint there was weak support for the inclusion of muscle tension, which showed the lowest prevalence among GAD cases and the least favorable sensitivity properties across the DSM-IV associated symptoms.…”
Section: Discussionsupporting
confidence: 87%
“…[40,41,63] Children experiencing GAD symptoms also worry more pervasively than children experiencing symptoms of other anxiety disorders and nonanxious controls. [28,[64][65][66] They do however worry about the same events/ activities, including personal health, family, and school, as nonanxious children but at a greater intensity. [67][68][69] Reports since the release of DSM-IV are consistent with these findings upon which the DSM-IV Anxiety Work Group adult criteria reviews relied.…”
Section: Dsm-v Options For the Excessiveness Requirementmentioning
confidence: 99%
“…A similar rate of comorbidity of 86% was found in a nonclinical sample of 49 youth diagnosed with GAD. 19 There were differences in the pattern of comorbidity between the clinical and nonclinical samples. Depression was diagnosed in 56% of the clinical sample and was the most common comorbid disorder.…”
Section: Anxiety Disorders and Ptsd Updatementioning
confidence: 96%
“…Common domains of worry in children with GAD include health of significant others, personal performance, family matters, and world issues. 19 Because the number of associated symptoms differentiates DSM-IV-TR criteria for GAD in children and adults, this domain has been an area of interest. Research has consistently shown that youth diagnosed with GAD typically endorse more than one associated symptom.…”
Section: Generalized Anxiety Disorder Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation